2009
DOI: 10.1103/physrevb.79.075424
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the atomic contribution to the Rashba spin-orbit splitting in surface alloys: Sb/Ag(111)

Abstract: We have studied the electronic structure of the Ag͑111͒͑ ͱ 3 ϫ ͱ 3͒R30°-Sb surface alloy by angle-resolved photoemission. We find two hybrid surface bands, similar to the isostructural Ag͑111͒-Bi interface. The spinorbit coupling induced spin splitting in momentum space, however, is strongly reduced from the Bi case. First-principles and model band calculations correctly reproduce this difference. The present results illustrate the complex interplay of atomic and structural contributions at the origin of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
57
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 30 publications
9
57
1
Order By: Relevance
“…Furthermore, the spin signal along the x-direction is clearly symmetric with respect toΓ. These unexpected P x and P z signals closely resemble observations for the Sb induced surface reconstruction on Ag(111) [33], where it was found that spin-interference in the photoemission process can induce a spin signal perpendicular to the direction expected for a Rashba signal [34]. This effect is part of a wide range of photoemission processes that can induce a spin signal many of which are well understood and others which remain unclear at the moment [35].…”
supporting
confidence: 81%
“…Furthermore, the spin signal along the x-direction is clearly symmetric with respect toΓ. These unexpected P x and P z signals closely resemble observations for the Sb induced surface reconstruction on Ag(111) [33], where it was found that spin-interference in the photoemission process can induce a spin signal perpendicular to the direction expected for a Rashba signal [34]. This effect is part of a wide range of photoemission processes that can induce a spin signal many of which are well understood and others which remain unclear at the moment [35].…”
supporting
confidence: 81%
“…However, as reported in that study, the Ge/Ag surface alloy shows an unexpected surface band split at theM points along the¯ KM line of the Ý3 × Ý3 surface Brillouin zone (SBZ). The observation of split bands at theM points clearly indicates that the Ge/Ag alloy differs substantially from the other group IV alloys (Pb/Ag [11] and Sn/Ag [3]; as well as from the alloys induced by Bi [2] or Sb [12]). As was concluded in Ref.…”
Section: Introductionmentioning
confidence: 92%
“…Decorating the surfaces with different atoms/adlayers modifies the Rashba-type spin splitting in the states at the surface, e. g. (Ar, Kr, Xe) on Au(111) [13,14], Li on (W(110), Mo(110)) [10], (Au, Ag) layers on (W(110), Mo(110)) [15]. The biggest increase of the spin splitting up to now was achieved by surface alloying, where every third atom in a noble metal (111) surface (Ag(111) [16][17][18][19][20][21][22] or Cu(111) [20,23]) is replaced by a heavy alloy atom (Bi, Pb and Sb). These surface alloys exhibit a spin splitting that is orders of magnitude larger than, e. g. in semiconductor heterostructures [17].…”
Section: Introductionmentioning
confidence: 99%